Web-based data exchange system in chemical process engineering - Liew, Syh Yeh; Kamsah, Mohd Zaki (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Chemical engineering process is a very complex task. Fortunately, there are many different types of computer-aided system that have been developed used in chemical process activities. These software packages have improved chemical engineering design enormously and enabled process engineers to optimize design strategies and plant performance. However, the software packages generated and used different type of data. Therefore, these individual systems can not share the data fed to, and generated by, other application systems. A lot of time is spent on transferring the data manually from one application to another. The manual data transfer is time consuming and error-prone. Globalization makes the communication around the world becomes paramount nowadays. It is essential for engineers to exchange or sharing information around the world. This paper presents the exploration and implementation of the new technology-eXtensible Markup Language (XML) in chemical process engineering. XML is used as the neutral file format for data exchange to solve the problems above. XML file format is a very powerful data exchange format because it is platform-independent, self-describing and the data can be shared between programs without coordination. A web-based client/server data access will be developed to demonstrate the potential and benefits of the XML and Internet in chemical process engineering.